Polityka oświatowa w Zielonej Górze w pierwszym dziesięcioleciu powojennym = Educational policy in Zielona Góra in the first post-war decade - Zaradny, Ryszard (Zielona Góra: Lubuskie Towarzystwo Naukowe)
A very difficult social and material situation as well as problems with qualified professional manpower created the necessity to look for unconventional solutions. After the war trauma there was a shortage not only of professional manpower securing the reconstruction of the country, but first of all the lack of teachers being able to educate the new human resources. The difficulties were cumulated in the so-called Regained Territories.
Keywords: Zielona Góra; polityka oświatowa; po 1944 r.